Religion, politics and educational system - Jovović, Zoran (Sociološki pregled, 2023)
Religion is important for a person’s life, as well as politics, which is a practical necessity. For religion, we can say that it is the need of every individual in the social community; it is simply a spiritual need. Both politics and religion prove to be human necessities. Both upbringing and education are also human necessities, while knowledge is in their centre. A reasonable educational system must meet the following conditions: pass on the cultural heritage to younger generations; prepare young individuals to assume some of the operational roles in society; create value awareness and conscience in young individuals; enable the unhindered development of the possibilities of each individual (meaning intellect, morals, culture); provide conditions for the unhindered acquisition and expansion of knowledge about and from religion; provide requirements for acquiring knowledge in politics and democracy (the rule of law, free market of ideas). Without religion, upbringing, and education, society lacks air, pure truths about it. Without religion, upbringing, and education, darkness would move into all of us and build a specific form for itself: we would make a pact “that binds us to the ninth circle of hell”. Those dark expectations would come true; what we fear most would come true for us. As Šušnjić (1997, p. 18) says, we live in a “century that has gambled away its human possibilities,” it is a bloody age. We are witnessing a time when most blood is shed: “we are losing our heads, while we have plenty of cutthroats” (Čupić, 2002, p. 18). This is an age of numbers, organizations, violence, even in the educational system; an age in which we have almost lost a clear idea of what we should do, that is, what we want and what we can do.